Comparing absorbed doses and radiation risk of the α-emitting bone-seekers [223Ra]RaCl2 and [224Ra]RaCl2 - Michael Lassmann; Uta Eberlein (Frontiers in Medicine, 2023)
[223Ra]RaCl2 and [224Ra]RaCl2 are bone seekers, emitting high LET, and short range (< 100 μm) alpha-particles. Both radionuclides show similar decay properties; the total alpha energies are comparable (223Ra: ≈28 MeV, 224Ra: ≈26 MeV). [224Ra]RaCl2 has been used from the mid-1940s until 1990 for treating different bone and joint diseases with activities of up to approximately 50 MBq [224Ra]RaCl2. In 2013 [223Ra]RaCl2 obtained marketing authorization by the FDA and by the European Union for the treatment of metastatic prostate cancer with an activity to administer of 0.055 MBq per kg body weight for six cycles. For intravenous injections in humans a model calculation using the biokinetic model of ICRP67 shows a ratio of organ absorbed dose coefficients (224Ra:223Ra) between 0.37 (liver) and 0.97 except for the kidneys (2.27) and blood (1.57). For the red marrow as primary organ-at-risk, the ratio is 0.57. The differences are mainly caused be the differing half-lives of the decay products of both radium isotopes. Both radionuclides show comparable DNA damage patterns in peripheral blood mononuclear cells after internal ex-vivo irradiation. Data on the long-term radiation-associated side effects are only available for treatment with [224Ra]RaCl2. Two epidemiological studies followed two patient groups treated with [224Ra]RaCl2 for more than 25 years. One of them was the “Spiess study”, a cohort of 899 juvenile patients who received several injections of [224Ra]RaCl2 with a mean specific activity of 0.66 MBq/kg. Another patient group of ankylosing spondylitis patients was treated with 10 repeated intravenous injections of [224Ra]RaCl2, 1 MBq each, 1 week apart. In total 1,471 of these patients were followed-up in the “Wick study”. In both studies, an increased cancer mortality by leukemia and solid cancers was observed. Similar considerations on long-term effects likely apply to [223Ra]RaCl2 as well since the biokinetics are similar and the absorbed doses in the same range. However, this increased risk will most likely not be observed due to the much shorter life expectancy of prostate cancer patients treated with [223Ra]RaCl2.